Engineering Escherichia coli for the production of adipic acid through the reversed β-oxidation pathway. Issue 12 (December 2015) - Babu, Thirumalaisamy; Yun, Eun Ju; Kim, Sooah; Kim, Do Hyoung; Liu, Kwang Hyeon; Kim, Soo Rin; Kim, Kyoung Heon
Graphical abstract: Highlights: A synthetic pathway for producing adipic acid in E. coli is proposed. Each step of the pathway was confirmed in vitro . Adipic acid production by the engineered E. coli was demonstrated. Abstract: The current study aimed to construct a functionally reversed β-oxidation cycle in Escherichia coli for the production of adipic acid, one of the most important dicarboxylic acids. Starting from the condensation of acetyl-CoA and succinyl-CoA, a synthetic pathway mimicking a reversed β-oxidation cycle was constructed in E. coli to produce adipyl-CoA, consisting of four enzymatic steps. Products of the synthetic pathway were confirmed by liquid chromatography-tandem mass spectrometry. To convert adipyl-CoA into adipic acid, a putative adipyl-CoA thioesterase (encoded by Acot8 from Mus musculus ) was selected, and its functional expression in E. coli was confirmed by gas chromatography-mass spectrometry. Finally, when the reversed β-oxidation cycle and Acot8 were co-expressed in E. coli, the resulting strain produced 12 μg/L of adipic acid from glucose. These results suggest that the synthetic adipic acid pathway functions in E. coli but requires further optimization for increased production of adipic acid.